Immunization Coverage and Barriers among Hajj and Umrah Pilgrims: Insights into Vaccine Uptake and Compliance - Adeeb A. Bulkhi; Hani M. Almoallim; Majed S. Obaid; Nahla H. Hariri; Hamsah S. Alqashqri; Ismail A. Alghamdi; Amar Mohammad A. Alkhotani; Muhammad Irfanullah Siddiqui; Heba M. Adly; Mohammed A. Garout; Elbagir A. Elfaki; Saleh A. K. Saleh; et al. (Journal of Epidemiology and Global Health)
Abstract Background The Hajj pilgrimage poses significant public health challenges due to the risk of infectious disease transmission. Despite mandatory vaccination policies, barriers such as hesitancy, logistical issues, and vaccine availability persist. Objective This study assesses vaccine uptake, reasons for compliance or non-compliance, and barriers among Hajj pilgrims. Methods A cross-sectional study was conducted during the 2024 Hajj season, with data collected via structured interviews from 5,355 participants. Descriptive statistics and logistic regression analyzed vaccination status and influencing factors. Results Of the participants, 4298 (80.3%) reported receiving mandatory or recommended vaccines, including influenza, COVID-19, and meningococcal. Primary motivators for vaccination were compliance to mandatory requirements 2240 (52.1%) and healthcare provider recommendations 2018 (46.9%). Among non-vaccinated respondents, the main reasons included belief in vaccine ineffectiveness 250(23.7%), reliance on natural immunity 243(23%), and lack of awareness 174(16.5%). Common barriers included long wait times 721(13.5%) and limited access to vaccination centers 543(10.1%). Women and individuals with higher education demonstrated greater vaccine uptake, while logistical barriers were more prevalent among self-employed and less-educated participants. Conclusion Despite high vaccine uptake, barriers remain. Addressing hesitancy, improving access, and aligning vaccine availability with Hajj timing are essential to enhance coverage and reduce disease transmission risks. Clinical Trial Number Not applicable.